Peace is much more than doves : the economic benefits of bird-based tourism as a result of the peace treaty in Colombia (2017)
Colombia has the greatest bird diversity of any country in the world, with approximately 20% of all bird species worldwide. Advances made by the Colombian government to end longstanding armed conflict and to promote ecotourism can help position Colombia as one of the most important bird watching destinations. This study estimates the economic benefits derived from peace in Colombia through the value that members of the US-based National Audubon Society place on a birding tour of Northern Colombia¿s Caribbean coast. The study analyzes preferences for a tour that includes the participation of local communities (some of whom were victims of the armed conflict), and visits to areas of importance for bird watching that would offer greater accessibility and safety for visitors after the Peace Agreement. Through the application of the contingent valuation method, results show that birding enthusiasts would be willing to pay, on average, an additional $60 per day and per person for a tour inside Colombia, as compared to a similar tour in Costa Rica. In addition to confirming demand for bird-based travel, the study provides information about potential visitors' preferences, which can help guide the development of a strategy to promote bird-based tourism to Colombia.